Biosynthesis silver nanoparticle using Bacillus thuringiensis strain BT2 and its potential use against Spodoptera frugiperda J.E. Smith (Lepidoptera: Noctuidae) - Khoiri Syaiful; Rahmawati Isna Nur; Djunaedy Achmad; Pawana Gita; Megasari Dita (BIO Web of Conferences)
Spodoptera frugiperda J. E. Smith is a new invasive pest in Indonesia and is reported to be invasive almost worldwide. One of the controls carried out is using synthetic pesticides. However, using synthetic pesticides causes problems, such as resistance, product and environment contamination, and environmental damage. Nanotechnology is a modern research field that has the potential to be used as an alternative pest control technology, one of which is silver nanoparticles. However, the biological synthesis of nanosilver is still limited. This research aims to determine the ability of Bacillus thuringiensis as a reductant in the formation of silver nanoparticles and to test its activity as an insecticide against S. frugiperda. The method was conducted by detecting reductant produced by B. thuringiensis by mixing 5 mL of 0.01 M AgNO3 with 45 mL each of supernatant and bacterial pellet. The mixed solution was then shaken for 3 days at a rotation speed of 150 rpm until a color change occurred in the solution. The AgNP synthesis results were characterized using a UV-Vis spectrophotometer. The results showed that based on spectrophotometer measurements it was confirmed that AgNPs synthesized with B. thuringiensis reductants showed a maximum absorption peak at a wavelength of 412.9 nm. AgNPs were tested on S. frugiperda using various concentrations. The highest mortality values were obtained in the treatment of 10% AgNPs with larval mortality of 47%. The LC50.90 values of 10.99% and 91.83%. The LT50.90 values were 78.10 hours and 145,12 hours. These results indicate that bio-synthesize silver nanoparticles have the potential to be used as a bioinsecticide.